2011
DOI: 10.1016/j.ejcts.2010.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Logistic risk model predicting postoperative renal failure requiring dialysis in cardiac surgery patients☆

Abstract: Renal failure requiring dialysis remains a serious complication, particularly in patients with pulmonary hypertension and previous renal dysfunction. Our logistic risk model allows the prediction of renal failure requiring dialysis, based on the individual presentation of risk factors and, therefore, helps to determine the perioperative risk in cardiac surgery patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 25 publications
(24 reference statements)
2
49
0
1
Order By: Relevance
“…[4] Prior studies have largely investigated clinical risk factors for new onset of dialysis-dependent renal failure occurring during the post-operative period after cardiac surgery. Clinical risk factors have included older age,[7, 13] sex,[11] race,[7] diabetes,[79, 13, 20, 21] peripheral vascular disease,[21, 22] baseline eGFR[9, 22] (or baseline SCr),[68, 13, 20, 21] poor ejection fraction,[6, 8, 9, 22] New York Heart Association class,[68, 13, 21, 22] congestive heart failure,[11, 20] prior acute myocardial infarction,[7, 11, 21] atrial fibrillation,[21] lung disease or chronic obstructive pulmonary disease,[68, 22] pre-operative intra-aortic balloon pump,[6, 8, 9, 22] emergent surgery,[8, 9] type of surgery,[69, 13] reoperation,[68, 20, 22] and low cardiac output failure or use of more than two inotropes. [11, 13] Only three studies investigated perfusion characteristics such as cardiopulmonary bypass time >120 or >180 minutes.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Prior studies have largely investigated clinical risk factors for new onset of dialysis-dependent renal failure occurring during the post-operative period after cardiac surgery. Clinical risk factors have included older age,[7, 13] sex,[11] race,[7] diabetes,[79, 13, 20, 21] peripheral vascular disease,[21, 22] baseline eGFR[9, 22] (or baseline SCr),[68, 13, 20, 21] poor ejection fraction,[6, 8, 9, 22] New York Heart Association class,[68, 13, 21, 22] congestive heart failure,[11, 20] prior acute myocardial infarction,[7, 11, 21] atrial fibrillation,[21] lung disease or chronic obstructive pulmonary disease,[68, 22] pre-operative intra-aortic balloon pump,[6, 8, 9, 22] emergent surgery,[8, 9] type of surgery,[69, 13] reoperation,[68, 20, 22] and low cardiac output failure or use of more than two inotropes. [11, 13] Only three studies investigated perfusion characteristics such as cardiopulmonary bypass time >120 or >180 minutes.…”
Section: Commentmentioning
confidence: 99%
“…[11, 13] Only three studies investigated perfusion characteristics such as cardiopulmonary bypass time >120 or >180 minutes. [11, 13, 20, 21]…”
Section: Commentmentioning
confidence: 99%
“…Rahamanian and colleagues and Aronson S et al described congestive heart failure as a risk factor for the development of post-surgery ARF. 15,8 Lohr et al found that both "congestive heart failure" (CHF) and systolic blood pressure less than 110 mmHg were associated with mortality. 16 Lien and Chan found that "heart failure" influenced survival in a retrospective analysis of 58 patients in case of ARF.…”
Section: Discussionmentioning
confidence: 99%
“…16 According to Chertow GM, Thakar CV, Wijeysundra DN and Rahmanian PB and colleauges low ejection fraction is a risk factor for post cardiac surgery acute renal failure. 2,[13][14][15] The effects of diabetes mellitus on postoperative renal failure may be the result of renal parenchymal disease, such as glomerulonephritis. Out of 50 patients, only 2 patients were diabetic and post operatively acute renal failure was not seen in either of them.…”
Section: Discussionmentioning
confidence: 99%
“…AKI associated with a cardiac operation is known to confer increased risk for both early and late death [4][5][6][7][8]. Among those who develop AKI, renal replacement therapy is required in 1% to 5% of patients [1,4,9,10] and carries an associated mortality of 25% to 50% [10][11][12]. Patients who experience recovery of renal function after AKI associated with a cardiac operation are still vulnerable to significantly increased rates of long-term mortality and progression to chronic kidney disease [5].…”
mentioning
confidence: 99%